Estágio supervisionado obrigatório III relato de caso: hipotireoidismo em cão (Canis lupus familiaris) - Alves, Clara Emiliana Coelho (Universidade Federal Rural do Semi-Árido, 2019)
Enabling the Veterinary Medicine graduate to experience an everyday practice, the Mandatory Supervised Internship in Small Animal Clinic proposes to the professional tobe a greater comprehensiveness regarding the experience and plurality of the casuistry of several clinical alterations. In that sense, the aim was to report a case of hypothyroidism related to the routine of the Small Animal Medical Clinic at the Dix-Huit Rosado Maia Veterinary Hospital of the Semi-Arid Federal Rural University, 15 year-old mixed-breed dog, weighing 21.5 kg old, showing apathy, skin and coat changes (opaque and brittle and hair loss), drowsiness, weight gain unrelated to the diet, intolerance to cold, lipidemia and bradycardia. These clinical signs led to the suspicion of hypothyroidism and complementary tests were performed to confirm the diagnosis: complete blood count, serum biochemistry, thyroxine dosage (T4), radiography and echocardiogram. The thyroxine (T4) dosage revealed a low dose of said hormone (0.09 ng / dL), which together with clinical and laboratory changes, confirmed the clinical suspicion of hypothyroidism. Therefore, therapy with levothyroxine sodium orally administrated was instituted every 24 hours, for an undetermined period, and the dose was adapted until reaching the acceptable limit of the circulating hormone and, at last, it was maintained at 400 mcg. The T4 dosage was repeated on the animal on its thirtieth day of treatment, where the normalization of the dose and evident improvement in the animal’s clinical and physical aspects were observed, such as a significant reduction in apathy and resistance to cold, decrease in drowsiness, visible improvement in hair appearance; opposing what the animal presented initially: classical clinical signs of the disease in dogs. The prognosis was considered good and the animal adapted well to the treatment, being it for life. The importance of the supervised internship is notorious and indisputable, since it intermediates the connection between practice and theory, making it possible to acquire new and indispensable knowledge in the professional life.
Monografia
Keywords: Hipotireoidismo; Tiroxina (T4); Levotiroxina; Endocrinologia; Canis familiaris; Hypothyroidism; Thyroxine (T4); Levothyroxine; Endocrinology; Canis familiaris; CIENCIAS AGRARIAS::MEDICINA VETERINARIA